2012
DOI: 10.1111/j.1365-2966.2012.21859.x
|View full text |Cite
|
Sign up to set email alerts
|

On the astrophysical robustness of the neutron star merger r-process

Abstract: In this study we explore nucleosynthesis in the dynamic ejecta of compact binary mergers. We are particularly interested in the question how sensitive the resulting abundance patterns are to the parameters of the merging system. Therefore, we systematically investigate combinations of neutron star masses in the range from 1.0 to 2.0 M⊙ and, for completeness, we compare the results with those from two simulations of a neutron star black hole merger. The ejecta masses vary by a factor of 5 for the studied system… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
838
9
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 680 publications
(895 citation statements)
references
References 80 publications
47
838
9
1
Order By: Relevance
“…Recent studies [29][30][31][32]35] have indicated that the r process in NSMs produces a final abundance pattern that can be similar to the solar r-process abundances, but only for heavier A>130 nuclei.…”
Section: Current Models For the R-processmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies [29][30][31][32]35] have indicated that the r process in NSMs produces a final abundance pattern that can be similar to the solar r-process abundances, but only for heavier A>130 nuclei.…”
Section: Current Models For the R-processmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35]). The ejected matter from NSMs is very neutron-rich (⟨Z/A⟩ ≡ Y e ∼ 0.1).…”
Section: Current Models For the R-processmentioning
confidence: 99%
“…Both Newtonian simulations including neutrino (ν-) interactions (e.g. [3]) and relativistic simulations ignoring ν-interactions (e.g. [4]) have produced massive dynamical ejecta that were throughout neutron-rich enough to enable strong r-processing with fission recycling.…”
Section: Nucleosynthesis Relevant Outflow Componentsmentioning
confidence: 99%
“…Optical and near-infrared observations of such an event, accompanying the short-duration GRB130603B have been reported [71] (see also [4]). After the first detailed nucleosynthesis predictions (following ideas of [33]) of such an event [13], many more and more sophisticated investigations have been undertaken, involving quite a number of authors [5,12,16,17,27,32,39,42,51,56,61,78] as well as the black hole accretion disk system after the formation of a central black hole [27,70,78,82].…”
Section: Neutron Star Mergersmentioning
confidence: 99%
“…Non-relativistic simulations (e.g. [32,61]) lead to large amounts of ejecta of the order 10 −2 M ⊙ with very small Y e -values of 0.04 and less. This causes a very strong r-process with fission cycling.…”
Section: Neutron Star Mergersmentioning
confidence: 99%